Spiritual journey of Murut Tahol in Sabah and its effect to their headhunting practice - Abd Hakim Mohad (2016)
Religion has a strong influence on the world view of a society. It also affects the actions and practices of everyday life. Therefore, changes in the religion also result in changes in religious practice. This paper tries to see the impact of religious change on headhunting (antaboh) in Tahol Murut community, Ulu Tomani, Sabah, Malaysia. This is because, originally, these people are holding on to faith-based ancestral spirits. Headhunting (antaboh) that they practiced for a long time, is based on traditional religion and belief which has existed for many generations. However, having come into contact with the Lun Bawang people who are Christians, they eventually were drawn to accept Christianity as their religion beganning around the 1950s. Thus, the effect of changes in religion in this community is interesting to be discussed. At least we can assess whether the view that religious change gives impact on the culture of a community also applies to this community. The Methodology used in this study is qualitative in nature involving library research and interview key informants. The researcher also had the opportunity to be with this community on a regular basis from 2003 until today. The result of this study revealed that religious change of Murut Tahol community give significant effect to their headhunting practice.